Manajemen desain fasilitas publik multifungsi yang aman di RTH Surabaya dengan Metode Function-Behavior-Structure - Richo, Yosef; Rizky, Desita; Khoirun Nisa, Fika (Institut Seni Indonesia Yogyakarta, 2024)
This research attempts to study the management of multifunctional furniture design in urban parks. Multifunctional furnitureis a product that can be used for various activities, but it is essential to consider the This research attempts to study the management of multifunctional furniture design in urban parks. Multifunctional furniture is a product that can be used for various activities, but it is essential to consider the design safety standards, especially from the aspect of its functionality design, because this furniture is located in crowded public areas. Field reviews show that many product facility designs have inadequate safety and comfort standards, which can adversely affect visitors, such as injuries, accidents, and negative behaviors and perceptions. Based on this, the research aims to align the management process of the functional design of urban park facilities with the visitors' motivation for activities. In the audit process, the researcher uses the concept development principles of the Function-Behavior-Structure (FBS) method, which is a theory of product design safety activation to determine priority facilities that need attention based on the types of design elements used. This research was conducted in a comprehensive type park in the city of Surabaya, specifically the Surabaya Zoo (KBS), using quantitative descriptive analysis methods. The results of this study indicate the need for recommendations for facility product designs that are safer and more functional.